3
$\begingroup$

Let $E$ be an infinite-dimensional complex Hilbert space and $A,B\in \mathcal{L}(E)$.

Why it is impossible to find $c\in \mathbb{C}^*$ such that $[A,B]=cI$?

$\endgroup$
  • $\begingroup$ Whats wrong with this answer mathoverflow.net/questions/293852/… ? $\endgroup$ – user42761 Mar 4 '18 at 9:15
  • 2
    $\begingroup$ @AndréS. I don't understand the relationship between my question and the link? Thank you $\endgroup$ – Student Mar 4 '18 at 10:22
3
$\begingroup$

First of all, suppose that

$[A, B] = I; \tag 1$

this implies $B \ne 0$; it also implies

$[A, B^n] = nB^{n - 1}, \; B^{n - 1} \ne 0, \tag 2$

which may be seen as follows:

$AB - BA = [A, B] = I \Longrightarrow AB^2 - BAB = B \ne 0; \tag 3$

since

$AB = BA + I, \tag 4$

we have

$AB^2 - B^2A - B = AB^2 - B(BA + I) = AB^2 - BAB = B \ne 0, \tag 5$

or

$AB^2 - B^2A = 2B \ne 0; \tag 6$

we may now proceed by induction: if

$AB^k - B^kA = kB^{k - 1} \ne 0, \tag 7$

$AB^{k + 1} - B^k AB = kB^k \ne 0, \tag 8$

since if $B^k = 0$, (7) would imply $B^{k - 1} = 0$; thus, again using $AB = BA +I$,

$AB^{k + 1} - B^{k + 1}A - B^k = AB^{k + 1} - B^k(BA + I) = AB^{k + 1} - B^kAB = kB^k \ne 0, \tag 9$

$AB^{k + 1} - B^{k + 1}A = (k + 1)B^k \ne 0; \tag{10}$

we therefore see that

$AB^n - B^nA = n B^{n - 1} \ne 0, \tag{11}$

holding for all positive integers $n$; taking norms yields

$n\Vert B^{n - 1} \Vert = \Vert n B^{n - 1} \Vert = \Vert AB^n - B^ nA \Vert$ $\le \Vert AB^n \Vert + \Vert B^nA \Vert \le 2 \Vert A \Vert \Vert B^n \Vert \le 2 \Vert A \Vert \Vert B \Vert \Vert B^{n - 1} \Vert \ne 0; \tag{12}$

since $\Vert B^{n - 1} \Vert \ne 0$ we may divide it out to find

$n \le 2 \Vert A \Vert \Vert B \Vert, \tag{13}$

a contradiction since $n$ may be arbitrarily large. Thus we cannot have (1), and this precludes

$[A, B] = cI, \; 0 \ne c \in \Bbb C,\tag{14}$

since it may be written

$[A, c^{-1}B] = I, \tag{15}$

thus reducing (14) to the case (1).

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Could you please give a reference in which I find the proof of the following result: the commutant of two bounded operators cannot be a non-zero multiple of the identity? Because I want to cite it in my paper. Thank you $\endgroup$ – Student Mar 16 '18 at 15:47
  • $\begingroup$ I thought about that question as I wrote the answer. I think the result is well-known but I don't know of any of the usual texts which have it. The nearest thing to a proof is in P.A.M. DIrac's Prinicple's of Quantum Mechanics, 4th edition, section 34 The Harmonic Oscillator. He gives a proof of similar results. $\endgroup$ – Robert Lewis Mar 16 '18 at 16:06
  • $\begingroup$ unfortunately, in section 34 of 'The Harmonic Oscillator' I don't find the desired proof. It is possible to use the result in my paper without citing it? Thank you $\endgroup$ – Student Mar 16 '18 at 16:26
  • $\begingroup$ @Student: If you read the section carefully you will see he does something similar with the operators $\eta$, $\bar \eta$ he defines. He shows that $[\bar \eta, \eta ] = 1$ and $[\bar \eta, \eta^n] = n \eta^{n - 1}$, which is essentially my equation (11). $\endgroup$ – Robert Lewis Mar 16 '18 at 16:38
  • $\begingroup$ Anyway, you could cite Dirac and say it's sort of similar, you could cite an online source such as MSE or google up something else; I think the proof is around. YOu might google search for other citings. Or you could say something like "this result is well-known but the proof does not seem to appear in the literature", or provide a proof yourself in a footnote. I think the result is pretty well-known. Anyway, you might ask a person more acquainted with the nuances of academic publishing than yours truly. $\endgroup$ – Robert Lewis Mar 16 '18 at 16:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.